A biological process effective for the conversion of CO-containing industrial waste gas to acetate. (July 2016) - Kim, Tae Wan; Bae, Seung Seob; Lee, Jin Woo; Lee, Sung-Mok; Lee, Jung-Hyun; Lee, Hyun Sook; Kang, Sung Gyun
Highlights: A two-stage culture consisting of carboxydotrophic archaea and homoacetogenic bacteria is proposed. The inhibitory effect of CO to an acetogen was measured. The conversion of LDG gas containing ca. 56% CO derived from steel-mill process was demonstrated by the two-stage culture. Abstract: Acetogens have often been observed to be inhibited by CO above an inhibition threshold concentration. In this study, a two-stage culture consisting of carboxydotrophic archaea and homoacetogenic bacteria is found to be effective in converting industrial waste gas derived from a steel mill process. In the first stage, Thermococcus onnurineus could grow on the Linz-Donawitz converter gas (LDG) containing ca. 56% CO as a sole energy source, converting the CO into H2 and CO2 . Then, in the second stage, Thermoanaerobacter kivui could grow on the off-gas from the first stage culture, consuming the H2 and CO in the off-gas completely and producing acetate as a main product. T. kivui alone could not grow on the LDG gas. This work represents the first demonstration of acetate production using steel mill waste gas by a two-stage culture of carboxydotrophic hydrogenogenic microbes and homoacetogenic bacteria.